A simple method for the synthesis of nanosized Ti3AlC2 powder in NaCl–KCl molten salt. Issue 9 (2nd September 2019) - Yang, Ling Xu; Wang, Ying; Zhang, Hai Liang; Liu, Hui Jun; Zeng, Chao Liu
ABSTRACT: Herein we report, a simple novel method to synthesize nanosized Ti3 AlC2 powder from Ti, Al, and C powders in NaCl–KCl molten salt. It is more conducive to the formation of Ti3 AlC2 at higher salt/precursor materials ratio and particle size of Ti3 AlC2 powder dramatically decreases with increasing mass ratio of the salt to precursor materials. Fine-grained Ti3 AlC2 powder is successfully synthesized at 950 ○ C for 5 h or at 1000 ○ C for 2 h with a salt/precursor materials ratio of 10:1. Ti3 C2 MXene is also prepared by etching fine-grained Ti3 AlC2 precursor in HF solution at 60°C for 2 h. GRAPHICAL ABSTRACT: IMPACT STATEMENT: It is the first time that nanosized ternary carbide Ti3 AlC2 powder has been synthesized by a simple, high efficiency and relatively low-temperature process.